BUSINESS RISK, DIVIDEND POLICY, CAPITAL STRUCTURE ON FINANCIAL PERFORMANCE: A STUDY IN INDONESIAN PHARMACEUTICAL COMPANIES - Nurasik; Endra Wahyu Ningdiyah; Wiwit Hariyanto (International Journal of Economic Integration and Regional Competitiveness, 2024)
General Background: Financial performance is a key determinant of a company's success and sustainability, particularly in the pharmaceutical industry, which faces unique challenges such as regulatory requirements, innovation costs, and market competition. Specific Background: In Indonesia, the pharmaceutical sector has shown significant growth, but companies face risks related to business dynamics, financial decision-making, and investment strategies. Factors such as business risk, dividend policy, and capital structure are critical in shaping financial outcomes. Knowledge Gap: Despite extensive studies on financial performance determinants, limited research focuses on how these factors interact specifically within the Indonesian pharmaceutical context, particularly over recent years. Aims: This study aims to analyze the effects of business risk, dividend policy, and capital structure on financial performance in Indonesian pharmaceutical companies during the 2017–2023 period. Results: The findings reveal that business risk significantly impacts financial performance, highlighting the importance of risk management in operational and strategic planning. Similarly, dividend policy influences financial performance, underscoring the role of payout strategies in shareholder value creation. Capital structure also affects financial performance, indicating the critical balance required between debt and equity financing. Novelty: This research offers new insights into the interplay of these factors in the pharmaceutical sector, using a focused dataset of eight companies, and provides empirical evidence specific to the Indonesian market. Implications: The study suggests that pharmaceutical companies must adopt comprehensive financial management practices to mitigate risks, optimize capital structures, and design effective dividend policies. Policymakers and industry stakeholders can use these findings to develop frameworks that support sustainable growth in the pharmaceutical sector. Further research could expand on this foundation to explore other factors influencing financial performance across different industries and regions.